Optimizing Process Conditions for Stingless Bee (Melipona irridipennis) Mead Fermentation Using Plackett-Burman Design and Response Surface Methodology - Srimeena, N.; Gunasekaran, S.; Murugesan, R. (Asian Journal of Chemistry, 2015)
In present investigation, mead (honey wine) fermentation parameters were optimized by Placket-Burman design and response surface methodology (RSM). Eleven nutritional and fermentation parameters (TSS, pH, temperature, inoculum size, fermentation time, tartaric acid, di ammonium phosphate, potassium sodium tartrate, magnesium sulphate, calcium sulphate and potassium meta bisulphate) were screened using Plackett-Burman experimental design were further optimized by central composite design of response surface methodology for maximizing the yield of ethanol in mead. Among the eleven independent variables TSS, temperature and fermentation time had high influence on the alcohol content. The maximum production of stingless bee mead obtained experimentally using the optimized parameters was 15 °Brix at 28 °C for 6 days which are in correlation with the predicted value. The model showed that the value of R2 (0.9991) was high and p-value of interaction of variance was < 0.0001. Hence the model can be said to be of highly significant.